Aminoglycoside-resistant mutants of Pseudomonas aeruginosa deficient in cytochrome d, nitrite reductase, and aerobic transport. - Bryan, L E (1981)
Two gentamicin-resistant mutants of Pseudomonas aeruginosa PAO 503 were selected after ethyl methane sulfonate mutagenesis. Mutant PAO 2403 had significantly increased resistance to aminoglycoside but not to other antibiotics. Mutant PAO 2402 showed a similar spectrum of resistance but of lower magnitude. Both mutants showed no detectable cytochrome d and had a high frequency of reversion to a fully wild-type phenotype. PAO 2403 had a marked decrease and PAO 2402 had a moderate decrease in nitrite reductase activity. Both mutants had reduced uptake of gentamicin and dihydrostreptomycin. Mutant PAO 2403 showed a general decrease in transport rate of cationic compounds, whereas mutant PAO 2402 had only deficient glucose transport. Both mutants showed enhanced rates of glutamine transport and no change in glutamic acid transport. Other components of electron transport and oxidative phosphorylation were normal. These mutants involve ferrocytochrome C551 oxidoreductase formed only on anaerobic growth but illustrate transport defects in aerobically grown cells.